Modeling Urban Atmospheric Lead Dispersion from a Mining Tailings Basin in Bahia, Brazil - Santos, Nelize Lima; Klammler, Harald Rene; Leal, Luiz Rogério Bastos (Anuário do Instituto de Geociências, 2022)
After the exhaustion of the lead mine in Boquira, Bahia in the 1990s, mining support structures and the tailings basin were abandoned, resulting in one of the largest environmental liabilities from mining in the state. Detailed studies on environmental damages are inexistent and this article aimed to analyze lead contamination in the urban area of the municipality, based on atmospheric dispersion modeling. For this purpose, a model was elaborated and implemented in Matlab R2014a considering houses, streets and air as three coexisting spatial domains. The model uses wind speed and direction as input data and results were calibrated (RMSE = 0.64 on decadal logarithmic scale) against existing measurements taken in 2014 of lead concentrations in street sediments and house dust within the urban area. Results suggested that particulate resuspension from streets and accumulation in houses may explain observed concentration patterns, and that the amount of suspended lead in the air is small compared to that in streets and houses. Additional simulations carried out for a hypothetical future remediation scenario showed that after 200 days the concentrations in the air and in the streets decreased considerably, while they stopped accumulating in houses. Hence, the model may be a potentially useful tool to assist in the evaluation and management of this and other urban areas affected by contamination through atmospheric dispersion of particulates. Consistent with our model formulation, we recommend mass per area for lead concentrations in streets and houses as more meaningful units for exposure risk/intensity than ppm (mass per mass) of street sediment or house dust.